Using Parkrun Age Grading as an Indicator of Adolescent Health: A Pilot Cross-sectional Comparator Study - Dearing CG; Williams TR; Dearing GC (Bentham Open, 2024)
Background: Prescribing physical activity in parks and other nature settings improves health and well-being. Objective markers of health or health improvement in such a setting are required. Objective: To examine if Parkrun age grading is a marker for health in adolescents living in a high-deprivation area. Methods: Twenty-five adolescents, 17 female, and 8 male, were recruited from a high deprivation area. Subjects participated in testing for cardiorespiratory fitness, glycosylated haemoglobin (Hb1Ac), body composition, strength, perceived stress, and perceptions of family functioning. Within 8 days of testing, participants also completed a single 5000m Parkrun, which generated age and gender-specific Parkrun age grading scores. Participants were assigned to a high Parkrun age grading or a low Parkrun age grading group using the participant's Parkrun age grading median value, and then groups were compared. Results: Parkrun age grading had relationships with body fat (r=-0.65, p <.001), muscle mass (r=0.47, p=0.027), and Hb1Ac (r=-0.45, p=0.037). Hb1Ac was significantly (p=0.006) different between high Parkrun age grading (34.4 ± 2.9 mmol/mol) and low Parkrun age grading (38.1 ± 2.8 mmol/mol). Conclusion: Parkrun age grading is a marker for physical health in vulnerable adolescents, though not all aspects of health are captured.
Keywords: Physical activity; Adolescent health; Physical fitness; Parkrun age grading; cardiorespiratory fitness; glycosylated haemoglobin (Hb1Ac)